2007
DOI: 10.1677/joe-07-0160
|View full text |Cite
|
Sign up to set email alerts
|

Decreased lactation capacity and altered milk composition in insulin receptor substrate null mice is associated with decreased maternal body mass and reduced insulin-dependent phosphorylation of mammary Akt

Abstract: Expression of insulin receptor substrates (IRS)-1 and -2 within the mammary gland was found to be high at midlactation and dramatically decreased with mammary involution. This observation supports the hypothesis that these proteins are induced in the mammary gland with lactogenesis and involved in normal milk synthesis. To test this hypothesis, lactation capacity, along with indices of mammary secretory cell glucose metabolism and cell signaling were compared in normal mice and mice carrying targeted mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…In rodents, withdrawal of progesterone leads to both parturition and activation of copious milk secretion. Lactation itself depends on the increase in PRL and its receptor that occurs at secretory activation (23) as well as corticosterone and insulin (4,16). Although strong evidence for a role for the IGF-IR in both proliferation and differentiation during pregnancy has been presented (36,45), our studies provide the first clear evidence that the IR plays a more important role in late pregnancy.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In rodents, withdrawal of progesterone leads to both parturition and activation of copious milk secretion. Lactation itself depends on the increase in PRL and its receptor that occurs at secretory activation (23) as well as corticosterone and insulin (4,16). Although strong evidence for a role for the IGF-IR in both proliferation and differentiation during pregnancy has been presented (36,45), our studies provide the first clear evidence that the IR plays a more important role in late pregnancy.…”
Section: Discussionmentioning
confidence: 65%
“…We found that selective deletion of IR using Cre-lox technology in the mouse mammary epithelium reduces the rate of growth of pups suckled by IR fl/fl Cre ϩ dams by 74%. Insulin and IR are known to support milk production during lactation (4,16), so our studies cannot definitively attribute the entire reduction in growth rate to impaired mammary gland development. However, the 50% decrease in alveolar number and the 60% decrease in staining for casein and lipid droplets at midpregnancy would suggest that the IR mediates both proliferative and differentiation phases.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The ERK/MAPK signaling pathway is thought not to be activated by insulin, IGF-1, or PRL. These hormones are known to influence mammary differentiation and synthesis of milk components primarily via PI3-AKT and STAT signaling (9,21). That the ERK/MAPK pathway is significantly enriched in the MFG gene list is very interesting and may support findings by Finlay et al (6) of its importance in MEC survival in the presence of insulin and cell-extracellular matrix (ECM) association.…”
Section: Discussionmentioning
confidence: 77%